2021
DOI: 10.1002/jcop.22710
|View full text |Cite
|
Sign up to set email alerts
|

Unequal childhoods in China: Parental education and children's time use

Abstract: Drawing on Lareau's binary conceptualization of parenting as concerted cultivation and accomplishment of natural growth, we examine how parental background determines the degree to which the two parenting practices are realized in China. To do so, we examine how parental education shapes children's weekly time use patterns on planned activities (academic and nonacademic) and unplanned activities. Using multi-level mixed-effects linear models based on the 2014 China Education Panel Survey, we find that parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 93 publications
(153 reference statements)
0
6
0
Order By: Relevance
“…However, with the transition to the market economy, privatization of educational resources, and implementation of the one-child policy (Mu & Hu, 2021), recent studies found sex equalizing trends in parental investment and greater educational opportunities for girls (Cheadle & Amato, 2011). Therefore, the male advantages in parental investment have been diminished.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with the transition to the market economy, privatization of educational resources, and implementation of the one-child policy (Mu & Hu, 2021), recent studies found sex equalizing trends in parental investment and greater educational opportunities for girls (Cheadle & Amato, 2011). Therefore, the male advantages in parental investment have been diminished.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the weak targeting and large regional variations in determining the recipience of dibao allowance, we hypothesize that children in bianyuan families reported greater suicidal ideation and lower developmental outcomes (mental health, physical health, and academic performance) than dibao families. Given the narrowing sex gap in parental investment (Mu & Hu, 2021), especially in education (Lin, 2019), we further hypothesize that male children have higher levels of suicidal ideation and lower levels of developmental outcomes than female children.…”
Section: Theoretical Framework and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this also meant that workingclass children did not get much training on speaking to people in power, challenging them, or advocating for themselves-skills that have high returns in higher education (Calarco 2014;Lareau 2011). In addition, upper class families pour a lot of resources into preparing their children for educational achievement by leveraging both their knowledge and networks within educational systems (Lareau 2015;Mu and Hu 2021). This intense investment by high resource families in the educational performance of their children can yield educational payoffs while also resulting in "hurried children" or children whose parents "overbook….drive them hard for academic achievement and expect them to act and respond like miniature adults" (Mendagudli and Sarawad 2021;422;Mu and Hu 2021).…”
Section: Family Socialization and Its Ties To Social Classmentioning
confidence: 99%
“…By taking parenting as the concerted cultivation and accomplishment of natural growth proposed by Lareau, Mu and Hu (2021) examine how parental education shapes their children's weekly time use patterns regarding planned and unplanned activities. Using the China Education Panel Survey from 2014, they show that parental education is positively associated with both planned academic and nonacademic activities, and negatively associated with the unplanned activities of children.…”
Section: Papers In This Special Issuementioning
confidence: 99%